High inflation and wage rigidity: The implicit response of the Italian tax-benefit system - Stefano Boscolo; Francesco Figari (University of Essex, Institute for Social and Economic Research (ISER), 2023)
We study the redistributive effect of inflation-induced revenue and expenditure variations in the Italian tax-benefit system in a context in which pensions and social transfers are indexed to inflation and nominal wage growth struggles to keep up. By means of the EUROMOD microsimulation model, we isolate the contribution of i) fiscal drag through the personal income tax, ii) indexation rules and policy changes regarding social insurance contributions and iii) pension and social transfer indexation rules related to the overall redistributive effect of the tax-benefit system and its vertical and horizontal components. The findings suggest that benefit indexation rules contribute to a non-negligible extent to income redistribution, that fiscal drag has a small regressive effect and that the implicit redistribution favours pensioners over private-sector employees.
Keywords: D31; H23; H24; 330; inflation; indexation; fiscal drag; redistribution; EUROMOD